Makiyah dan Madaniyah - Mufidah, Zahratul (Maliki Interdisciplinary Journal, 2025)
The verses of the Qur’an are divided into Makkiyah and Madaniyah verses because they were revealed at different times and locations with various backgrounds. This article aims to improve our understanding of the Qur’an and be able to distinguish Makkiyah and Madaniyah verses. The research method used is qualitative research with the type of literature study or library research. This literature study is carried out by accessing various references such as scientific journals, books, and articles related to makiyah and madaniyah. The results of this article concluded that Makiyah is a verse that was revealed before the Prophet Muhammad migrated, while if it was revealed after the Prophet Muhammad migrated it is called Madaniyyah. This is based on historical theory. In addition, there are also geographical, subjective, and content theories. The classification of Makkiyah and Madaniyah letters was carried out by scholars based on the history of the companions. One of the characteristics of Makkiyah verses generally discusses creed, monotheism, and the horror of doomsday. While madaniyah verses focus more on law, muamalah, and worship. The usefulness of knowing this is so that you can interpret the Qur’an correctly, recognize language styles, and so on.